2022
DOI: 10.21037/jtd-22-260
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic test: combined detection of heparin-binding protein, procalcitonin, and C-reactive protein to improve the diagnostic accuracy of bacterial respiratory tract infections

Abstract: Background: Respiratory tract infection (RTI) is one of the most common diseases worldwide, and its incidence is rising year by year due to environmental pollution. Sputum culture remains the gold standard for RTI diagnosis, but its performance is limited by difficulties related to the sampling and testing of the sputum specimens. Heparin-binding protein (HBP), procalcitonin (PCT), and C-reaction protein (CRP) are Inflammatory markers. They have the advantage of being fast, accurate and reproducible, but limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
1
4
0
1
Order By: Relevance
“…The HL test and Calibration curve results show that the multivariable logistic regression model has good fit and predictive ability. Our findings on the predictive value of HBP combined with other inflammatory indicators agree with those reported by Jin Ma et al, who discovered that adding HBP to other inflammatory markers enhanced prediction accuracy[19]. Furthermore, ROC analysis confirmed that the predictive value of the logistic regression model was superior to that of HBP alone, showing that HBP can be used as a better complementary indicator to existing inflammatory indicators.…”
supporting
confidence: 91%
“…The HL test and Calibration curve results show that the multivariable logistic regression model has good fit and predictive ability. Our findings on the predictive value of HBP combined with other inflammatory indicators agree with those reported by Jin Ma et al, who discovered that adding HBP to other inflammatory markers enhanced prediction accuracy[19]. Furthermore, ROC analysis confirmed that the predictive value of the logistic regression model was superior to that of HBP alone, showing that HBP can be used as a better complementary indicator to existing inflammatory indicators.…”
supporting
confidence: 91%
“…Previous findings have revealed that HBP is a marker of bacterial infection in adult patients. 27 , 28 However, a relatively small proportion of enrolled patients were diagnosed with bacterial infections in this study, and no patient was found to have positive blood culture. Therefore, we prespecified a sensitivity analysis excluding patients with bacterial infections.…”
Section: Discussionmentioning
confidence: 74%
“… 34 Linder 2011 [ 25 ] Prospective and retrospective multicenter cohort study Sweden 77 Inclusion criteria: patients with clinically suspected meningitis, who underwent a lumbar puncture March 2006 to November 2009 Lund University Hospital, Lund, Sweden NA CSF Diagnosis was based on classification of bacterial meningitis was based on the criteria of Durand. 20 Ma 2022 [ 14 ] Prospective case control study China 87 Inclusion criteria: (I) inpatient with complete clinical data at the Department of Respiratory Medicine of our hospital; (II) be aged ≥18 years; (III) for the case group, meet the diagnostic criteria for respiratory tract bacterial infection January 2019 to December 2019 Department of Respiratory Medicine of the East Hospital of Sichuan Provincial People’s Hospital On hospital admission Blood Diagnosis was based on RTI on the definition and diagnostic criteria for RTI set out in the Guidelines for the Diagnosis and Treatment of Respiratory Diseases. 24.17 Namiduru 2022 [ 11 ] Prospective study India 97 Inclusion criteria: Patients with meningitis admitted to University of Gaziantep Medicine Faculty Hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, elevated urinary HBP was significantly associated with the presence of urinary tract infections (UTI) in adults and children [ 12 , 13 ]. It was also reported to be of diagnostic value in respiratory tract infections (RTI) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%